Condições de oxigenação e desoxigenação de um trecho do Rio Uberabinha no município de Uberlândia - Almeida, Juliano da Silva Martins de (2013)
The conditions of life and preservation of fauna and flora of an aquatic environment are related to the concentrations of dissolved oxygen in the medium. Thus, the use of mathematical models in evaluating water quality become important tools for the study in this field. The present study aimed to quantify the surface reaeration coefficients (k2) and deoxygenation (k1) through mathematical modeling and experimental measurements associated with correlations in the literature in an urban stretch of 20.85 km of river Uberabinha, in Uberlândia -MG. For this sampling campaigns were carried out between April-October period of 2012 to obtain values of dissolved oxygen and temperature. Values were obtained even speed, altitude, slope, width, depth and Biochemical Oxygen Demand in time for 20 days. The surface reaeration coefficients were estimated total study excerpt, the same being divided into six distinct sections. In each section were selected for sampling different areas and applied statistical tests to compare blocks. The aim was to investigate possible differences in function of the positions of sampling and seasonal variation. We used the empirical equation of O\'Connor and Dobbins, Owens et al.; Melching and Flores. It was observed that equation O\'Connor and Dobbins set of sections better depth high, with little variance with results from the literature. Already equations Melching and Flores and Owens et al. adjusted better to the high speed sections showed that the stream flow and shallow blade. Deoxygenation coefficients were obtained in a urban stretch of 3000 meters, by adjusting the input variables: water temperature, dissolved oxygen deficit initial DBO20, k2 value, time and dissolved oxygen deficit in the final equation Streeter and Phelps. As additional mathematical support made up the balance of oxygen dissolved in a volume control, ignoring the rates of evaporation and infiltration into the soil to that sector. For the model of Streeter and Phelps observed the increase in the values of k1 with increasing flow rate and the balance of dissolved oxygen has been observed to increase the values of k1 with the volume reduction control, a point still being observed minimum in July.